Chemerin, Inflammatory, and Nitrooxidative Stress Marker Changes Six Months after Sleeve Gastrectomy. (11th April 2018) - Cӑtoi, Adriana Florinela; Pârvu, Alina Elena; Mironiuc, Aurel; Chiorescu, Ştefan; Crӑciun, Alexandra; Pop, Ioana Delia; Cӑtoi, Cornel
Abstract : Background . Chemerin is a chemokine known to be increased in morbidly obese (MO) patients and correlated with markers of inflammation and nitrooxidative stress. We aimed to evaluate the changes of serum chemerin six months after laparoscopic sleeve gastrectomy (SG) and to asses if these changes are accompanied by variations of inflammatory and nitrooxidative stress markers. Material and Methods . We investigated the levels of chemerin, high-sensitive C-reactive protein (hsCRP), tumor necrosis factor alpha (TNF- α ), nitrite and nitrate (NOx), total oxidant status (TOS), total antioxidant response (TAR), and oxidative stress index (OSI) in a group of 24 MO patients submitted to SG before and six months after surgery. The MO group was compared with 20 controls. Results . hsCRP (p < 0.001 ), NOx (p < 0.001 ), TOS (p < 0.001 ), TAR (p = 0.007 ), and OSI (p = 0.001 ) were significantly different between the two groups. Six months after surgery, we noticed significant changes (42.28% decrease) of hsCRP (p = 0.044 ) and OSI (p = 0.041 ) (31.81% decrease), while no significant changes were observed for chemerin (p = 0.605 ), TNF- α (p = 0.287 ), NOx (p = 0.137 ), TOS (p = 0.158 ), and TAR (p = 0.563 ). Conclusions . Our study showed no significant changes of chemerin, and except for hsCRP and OSI, no other inflammatory and nitrooxidative stress markers changed six months after surgery.